Is trust built on spirit? Examining spiritual leadership as a multidimensional predictor of organizational trust; pragmatic evidence from Malaysian public universities - Daud, Zulkiflee; Elsaman, Hosam Azat; Mutazam, Mazli; Sallehuddin, Mohd Rashdan; Haron, Nasiruddin; Abidin, Mohd Abidzar Zainol; Ahmad, Rusli (Frontiers in Psychology, 2025)
A lack of organizational trust has been consistently linked to deteriorating performance outcomes in academic institutions, particularly in administration staff in the Malaysian higher education sector, when trust is deficient that can lead to reduce the staff morale and negatively affect their motivation, this directly impact the whole organizational performance. This study examined the effect of spiritual leadership on organizational trust amongst administrative and support staff in a public university in Malaysia. The authors developed a conceptual model to interpret the relation between spiritual leadership and organizational trust. Stratified random sampling technique was used in data collection, with a sample size of 306 and data analyzed using statistical package of social science SPSS, thus, the study executed factor analysis and multiple regression analysis in validating and statistically detecting the significant effect between the spiritual leadership which significantly predicted and interpreted the organizational trust. The study variable hope is significantly influenced by all three dimensions of organizational trust which are leader’s reliance, leader’s behavior and harmony. This study contributes to the literature on how spiritual leadership influence the organizational trust particularly in public universities in Malaysia.